Kristologi disabilitas di kalangan brother and sister living with HIV-AIDS (BROSLIH) - Sarese, Andre Brian (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2022)
This paper is the result of a Christology of Disability studies on the understanding of Jesus according to the Brothers and Sisters living with HIV-AIDS (BROSLIH) at the Victory Plus Foundation, Yogyakarta. BROSLIH found a new perspective and meaning about the Image of Jesus Christ. Issues regarding stigma, discrimination, violence, and even loss of self-esteem brought BROSLIH out of the construction of a perfect understanding of Jesus. There are three main findings that will be put forward in this paper: First, Jesus is in solidarity with the lowly creation, through His Spirit in the lament of human suffering who prays to God in complex life situations. Second, BROSLIH who accepts rejection and various social injustices find the meaning of Jesus as the One who brings justice to those who are marginalized. Third: Jesus who is present in the souls of people who are broken and injured, is the meaning of the figure of Jesus who is present in BROSLIH's life and is depressed because of rejection from parents. AbstrakArtikel ini merupakan hasil dari kajian Kristologi Disabilitas terhadap pemahaman tentang Yesus menurut Brother and Sister living with HIV-AIDS (BROSLIH) di Yayasan Victory Plus Yogyakarta. BROSLIH menemukan cara pandang serta pemaknaan yang baru mengenai Citra Yesus Kristus. Persoalan mengenai stigma, diskriminasi, kekerasan bahkan hilangnya penghargaan diri membawa BROSLIH keluar dari konstruksi pemahaman mengenai Yesus yang sempurna. Terdapat tiga temuan utama yang akan dikedepankan dalam tulisan ini: Pertama, Yesus yang bersolidaritas kepada ciptaan yang hina, melalui Roh-Nya dalam ratapan penderitaan manusia yang berdoa kepada Allah dalam situasi kehidupan yang kompleks. Kedua, BROSLIH yang menerima penolakan serta berbagai ketidakadilan sosial menemukan makna Yesus sebagai Dia yang mendatangkan keadilan bagi mereka yang termarginalisasi. Ketiga: Yesus yang hadir dalam jiwa orang-orang yang hancur dan terluka, adalah pemaknaan terhadap sosok Yesus yang hadir dalam kehidupan BROSLIH yang mengalami depresi karena mendapat penolakan dari orang tua.